2008
DOI: 10.4196/kjpp.2008.12.3.101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ketamine on Catecholamine Secretion in the Perfused Rat Adrenal Medulla

Abstract: The aim of the present study was to examine the effects of ketamine, a dissociative anesthetics, on secretion of catecholamines (CA) secretion evoked by cholinergic stimulation from the perfused model of the isolated rat adrenal gland, and to establish its mechanism of action, and to compare ketamine effect with that of thiopental sodium, which is one of intravenous barbiturate anesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Alternatively, the anaesthesia and surgical procedure may have uncontrolled consequences on the basal release. Although ketamine does not modify basal catecholamine secretion 45 , a direct measurement of plasma catecholamines, in a freely moving mouse submitted or not to various stress paradigms, will be necessary to definitely answer this question. Although a direct cell-cell communication through gap junctions has been described in many endocrine/neuroendocrine tissues [46][47][48][49] , including the adrenal medulla 6,7,11 , its contribution to hormone secretion in vivo has been unambiguously established so far only for insulin 50,51 and renin 49,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the anaesthesia and surgical procedure may have uncontrolled consequences on the basal release. Although ketamine does not modify basal catecholamine secretion 45 , a direct measurement of plasma catecholamines, in a freely moving mouse submitted or not to various stress paradigms, will be necessary to definitely answer this question. Although a direct cell-cell communication through gap junctions has been described in many endocrine/neuroendocrine tissues [46][47][48][49] , including the adrenal medulla 6,7,11 , its contribution to hormone secretion in vivo has been unambiguously established so far only for insulin 50,51 and renin 49,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Thiopental administered at subanesthetic and anesthetic doses leads to oxidative stress in the brain striatum, likely because of the suppressed production of adrenaline, which causes systemic hypotension and associated high-risk complications [ 18 ]. Published studies have shown that, unlike ketamine, thiopental suppresses release of catecholamines [ 36 ] and decreases the amount of adrenaline in rats even at subanesthetic doses [ 16 ]. Furthermore, it was reported that hyperalgesia occurred in the animals receiving thiopental alone, while analgesia was observed in the animals receiving thiopental combined with adrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…This reveals that the amount of blood ADR should not fall below a certain level for TPS to be able to establish analgesic activity. TPS has also been reported to suppress catecholamine production in the literature [ 14 ]. Previous studies have also evaluated an increase rise in pain threshold as an analgesic activity and have reported that ADR induces significant analgesic activity [ 5 ].…”
Section: Discussionmentioning
confidence: 99%